2017 IEEE International Systems Engineering Symposium (ISSE) 2017
DOI: 10.1109/syseng.2017.8088275
|View full text |Cite
|
Sign up to set email alerts
|

MBSE approach to support and formalize mission alternatives generation and selection processes for hypersonic and suborbital transportation systems

Abstract: MBSE approach to support and formalize mission alternatives generation and selection processes for hypersonic and suborbital transportation systems ieee Publisher:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Mission simulation [36,37] is run at the end of each iteration, considering the highestfidelity aerodynamic data available at each design step. The software ASTOS (release 9.17), by Astos Solutions GmbH (Stuttgart, Germany), is used to perform the simulations.…”
Section: Mission Simulationmentioning
confidence: 99%
“…Mission simulation [36,37] is run at the end of each iteration, considering the highestfidelity aerodynamic data available at each design step. The software ASTOS (release 9.17), by Astos Solutions GmbH (Stuttgart, Germany), is used to perform the simulations.…”
Section: Mission Simulationmentioning
confidence: 99%
“…The mission design methodology adopted in this paper follows the guidelines of the model-based approach of Refs. [42,43]. The approach is highly oriented toward both functional analysis [42,44,45], and scenario-based assessments [46,47].…”
Section: An Mbse Approach To Mission Designmentioning
confidence: 99%
“…The described conceptual design methodology stemming from Refs. [42,43] has been used to define the mission objectives and constraints, to provide a first design box for the cave explorer, and to identify the mission architecture that will enable the lava tube exploration. These higher-level results will be briefly presented and discussed before diving into the parametric design of the cave explorer.…”
mentioning
confidence: 99%
“…Thus, this work has identified the potential areas for fuel consumption reduction, and research studies looked at historical facts about fuel consumption in the aviation sector (Seitz et al , 2021) are shown in Figure 2. Fusaro et al (2017a) emphasized and discussed model-based systems engineering, focusing on significant operational and technology constraints of air transport systems. Yanto and Liem (2018) have applied two-dimensional linear regression models, by using flight missions on different aircraft at certain gross weight (MTOW) and range (R).…”
Section: Introductionmentioning
confidence: 99%